COVID-19 Pandemic and Lockdown: Psychological Distress Impact amongst PCL Nursing Students of Nepalgunj Nursing Campus, Kohalpur, Banke, Nepal - Dhakal, Sanjeeva; Kharel, Prabha (Journal of Nepalgunj Medical College, 2022)
Introduction:  The uncontrolled spread of COVID-19 worldwide has confined millions of people to their homes. In addition to being a public physical health emergency, COVID-19 (Corona Virus Disease 2019) has significantly resulted in a large number of psychological distress and impacts. The career oriented professional students are away from their academic environment.Aims: This study aims to assess the psychological distress impact of the COVID-19 pandemic among the Proficiency Certificate Level Nursing of  Nepalgunj Nursing Campus, Kohalpur, Banke, Nepal.Methods: The online survey with a link directed to students of Proficiency Certificate Level (PCL) Nursing of Nepalgunj Nursing Campus, Kohalpur, Banke, Nepal  conducted during lockdown (July 16th –July 21st 2020) which was open for 6 days. Sociodemographic characteristics are the independent variables. Psychological distress was constructed using the Kessler Psychological Distress Scale (K10) Scale as a dependent variables. Data were analyzed using Microsoft Excel.Results: The evidence of the survey showed that in total 80.2, % (severely distressed - 30.7%, moderately distressed -29.7%, mildly distressed- 19.8%) of the Proficiency Certificate Level Nursing students of Nepalgunj Nursing Campus, were having psychological distress during COVID-19 pandemic and lockdown assessed by using K10 scale.Conclusion: The present study showed that Proficiency Certificate Level Nursing students were moderately and severely distressed during lockdown of Covid-19 pandemic.